2020
DOI: 10.1371/journal.pone.0225485
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the capacity of mesenchymal stromal cell lines to form spheroids

Abstract: Mesenchymal stem cells (MSC)-spheroid models favor maintenance of stemness, ex vivo expansion and transplantation efficacy. Spheroids may also be considered as useful surrogate models of the hematopoietic niche. However, accessibility to primary cells, from bone marrow (BM) or adipose tissues, may limit their experimental use and the lack of consistency in methods to form spheroids may affect data interpretation. In this study, we aimed to create a simple model by examining the ability of cell lines, from huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
6
8
0
Order By: Relevance
“…To further investigate the differences in cell number and to obtain spatial information about the location of dead cells, we performed a live/dead assay (Figure 3). We observed an increase in cell death on day 7 compared to day 1 in all culture systems, which was consistent with our DNA content result as well as other studies that have shown increase in cell death due to apoptosis when MSCs are cultured as aggregates under static conditions (Deynoux et al, 2020).…”
Section: F I G U R Esupporting
confidence: 93%
“…To further investigate the differences in cell number and to obtain spatial information about the location of dead cells, we performed a live/dead assay (Figure 3). We observed an increase in cell death on day 7 compared to day 1 in all culture systems, which was consistent with our DNA content result as well as other studies that have shown increase in cell death due to apoptosis when MSCs are cultured as aggregates under static conditions (Deynoux et al, 2020).…”
Section: F I G U R Esupporting
confidence: 93%
“…Many studies have reported that hypoxia prompted the self-renewal of MSCs [8][9][10][11]. This was consistent with our ndings which showed that the signi cantly higher OD values and clone numbers were detected in both AMSCs and BMSCs in the hypoxia group, compared with those in the normoxia group.…”
Section: Discussionsupporting
confidence: 92%
“…However, differentiation-inducing therapy of MSCs has been reported to be potential in treating tendon injury [2,6,7]. Among the various differentiation-inducing therapies, hypoxia has not only been found to promote the proliferation of MSCs [8][9][10][11], but also has shown to be an e cient inductor in tenogenic differentiation of MSCs in repairing tendon injury [8,12,13]. Many studies have found that hypoxia increased the number of MSCs and augmented the formation of colonies [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The spheroids are continuously rearranged and condensed 18. This is supported by experimental data that we and others have published 27 showing that spheroid size declines with cultivation time. Others have reported hMSC spheroid growth with cultivation time 28, but this also leads to an increasing number of single cells or smaller cell agglomerates in the supernatant, which can form new spheroids.…”
Section: Cultivation Of Hmscs As Spheroidssupporting
confidence: 77%